DESIGN, In silico Modeling, Toxicity study and Synthesis of Novel Substituted Semicarbazide Derivatives of Pyrimidine: An Antitubercular Agent - Mandhadi, Jithendar R.; Panneerselvam, Theivendren; Parasuraman, Pavadai (Current Bioactive Compounds, 2020)
Background: A series of 1-(2-(2-amino-5-carbamoyl-6-(1-(substitutedphenyl) prop-1-enyl) pyrimidin-4-yloxy)acetyl) semicarbazide (4a-i) derivatives was synthesized from substituted aromatic aldehydes, ethyl cyanoacetate and guanidine hydrochloride and characterized by analytical and spectral data, FTIR, 1H-NMR and Mass spectroscopy data. Methods: The antiTB action of the synthesized compounds was screened in comparison with the standard drug Rifampicin using MABA assay method. The SAR of substituted aromatic aldehydes with modification at ortho, meta and para positions with electron withdrawing group. Result: The compounds 1-(2-(2-amino-5- carbamoyl-6-(1-(2-fluorophenyl) prop-1-enyl) pyrimidin-4- yloxy) acetyl) semicarbazide and 1-(2-(2-amino- 5-carbamoyl-6-(1-(3-chlorophenyl) prop-1-enyl) pyrimidin-4-yloxy) acetyl) semicarbazide showed equal MIC values against Mycobacterium tuberculosis H37Ra with the value of 3.90μg/ml. Conclusion: The SAR study revealed that the antiTB activity of the synthesized compounds were affected by lipophilicity of the substituent.
Keywords: SAR